Addressing discriminatory benefit design for people living with HIV: a California case study. Issue 12 (2nd December 2017) - McMenamin, Sara B; Shimkhada, Riti; Hiller, Sarah P.; Corbett, Garen; Ponce, Ninez
ABSTRACT: Concern is growing in the United States regarding the potential for health insurance benefit designs to discriminate against persons living with HIV as research demonstrates that such practices are occurring. A recent complaint filed against health insurers in seven states alleges that some health insurance companies have been using benefit designs that discourage enrollment of people living with HIV either by not covering essential HIV medications or by requiring cost-sharing for these prohibitively expensive medications. Legislators across the country have reacted by introducing legislation to address these growing problems. This paper describes Assembly Bill 339, legislation passed in California in 2015 and going into effect on 1 January 2017, which provides protection for people living with HIV by requiring coverage for single-tablet regimens to manage HIV while placing a cap on patient cost-sharing. Given California's size and influence, and the uncertainty of the future of the Affordable Care Act, this legislation has the potential to influence the national policy debate.